Genetic association with clusters of persons with TDP‐43 proteinopathy. (December 2021) - Katsumata, Yuriko; Abner, Erin L; Karanth, Shama D; Teylan, Merilee A.; Mock, Charles; Kryscio, Richard J; Schmitt, Frederick A; Fardo, David W.; Nelson, Peter T
Abstract: Background: TAR‐DNA binding protein 43 kDa (TDP‐43) proteinopathy is a neurodegenerative pathology present in up to 50% of aged persons with dementia. Recently, a classification system for limbic‐predominant age‐related TDP‐43 encephalopathy neuropathologic changes (LATE‐NC) was proposed. In previous work, we reported that brains with TDP‐43 proteinopathy comprise four distinct clusters, based on clinical features and comorbid neuropathologies (PMID 32797255). All included participants (N=495) had autopsy‐confirmed TDP‐43 proteinopathy. Cluster 1 (n=103) contained mostly cases with a pathologic diagnosis of frontotemporal lobar degeneration (FTLD‐TDP). Cluster 2 (n=71) was distinguished by relatively "pure" LATE‐NC (i.e., no/low ADNC). Both Clusters 3 (n=114) and 4 (n=207) had high levels of ADNC + LATE‐NC; however, Cluster 4 featured earlier disease onset and swift disease progression without FTLD clinical features. Here, we investigate differences in genetic features between ADNC and LATE‐NC subclusters. Method: Participant data were drawn from the previously analyzed sample (N=495), which comprised of autopsied research volunteers who were followed at Alzheimer's Disease Research Centers and appear in the National Alzheimer's Coordinating Center database. Alzheimer's Disease Genetics Consortium (ADGC) data were linked to the initial sample, and we examined the association of single‐nucleotide polymorphisms (SNPs) identified as a late‐onset AD associated SNP by the International Genomics of Alzheimer's Disease Project genome wide‐association study in LATE‐NC clusters. Result: ADGC data were available for 124/495 participants. Of these, 89 were in Cluster 3 and 4 (ADNC+LATE‐NC) and 20 in Cluster 2 (pure LATE‐NC). The SNPs rs190982 located in MEF2C on Chromosome 5 and rs11218343 located in SORL1 on Chromosome 11 were significantly associated with cluster membership. The G allele of rs190982 and the C allele of rs11218343 were risk SNPs for Cluster 2. Conclusion: Two SNPs may be differentially associated with ADNC+LATE‐NC vs. pure LATE‐NC. Given that TDP‐43 proteinopathy is common in aged brains, identifying genetic factors is a crucial step toward developing disease‐modifying therapies. Although our final sample size was small, these results might help point to unsuspected pathways that influence ADNC and LATE‐NC phenotypes.